Transfer Pricing and Multinational Enterprises - Bondarenko, Mariia (2018)
This thesis focuses on the tax concept of transfer pricing. The main purpose of the thesis is to investigate the nature of transfer pricing both from companies’ and tax authorities’ perspective, focusing on the transfer pricing methods available in context of the OECD Guidelines, with the following comparison of the differences between the frameworks established in different countries through the detailed analysis of local legislations. In order to achieve this goal the basic characteristics of the transfer pricing phenomenon are examined; the process of transfer pricing is explained and the following research of the legislations of selected countries is conducted.